Increased risk of dementia differs across cardiovascular diseases and types of dementia - Data from a nationwide study - Kauko Anni; Engler Daniel; Niiranen Teemu; Ortega-Alonso Alfredo; Schnabel Renate B. (WILEY, 2025)
Aims
Dementia is a major health problem. Cardiovascular diseases (CVD) and risk factors are associated with incident dementia. However, whether there is an association among CVD, Alzheimer's disease (AD) and vascular dementia (VD) at the population level remains unclear.
Methods
We analysed the association between CVD (heart failure [HF], atrial fibrillation [AF], myocardial infarction [MI], peripheral arterial disease, stroke and transient ischemic attack) and the incidence of dementia using nationwide FinnGen data of 218,192 individuals. The last follow-up information on dementia was available from October 2021.
Results
The age at the end of the follow-up was 61.7 ± 17.1 years, and 53% were women. Overall, we observed 9701 (4.4%) dementia, 6323 (2.9%) AD and 1918 (0.7%) VD cases. Individuals with CVD had a higher risk of developing dementia than unexposed individuals. In the multivariable-adjusted Cox models, stroke was most strongly associated with dementia (hazard ratio [HR] 1.7, 95% confidence interval [CI] 1.6–1.8). CVD was more strongly associated with VD than with AD. Individuals with HF and MI had an increased risk of AD (HF: HR 1.11, 95% CI 1.04–1.19; MI: HR 1.10, 95% CI 1.02–1.18). AF was associated with VD (HR 1.58, 95% CI 1.42–1.77), but not with AD (HR 1.03, 95% CI 0.97–1.09). Clinical characteristics, such as diabetes, smoking and alcohol abuse, were associated with both types of dementia.
Conclusion
All major CVDs were associated with an increased risk of developing dementia, particularly VD. Therefore, CVD onset should prompt an assessment of cognitive decline and possible preventive measures.